New procedure to pre-select lactic acid bacteria able to control table-olive fermentation - Caridi, Andrea (2022)
Using 35 artisanal Calabrian table-olive brines, 153 strains of lactic acid bacteria were isolated. A screening procedure was designed, involving the following steps: 1) Gram stain, cellular morphology, homolactic fermentation, acidifying activity in MRS broth; 2) growth in olive paste with NaCl 11%; 3) increase of the antioxidant activity; 4) identification of the best strains. The proposed procedure allows an evaluation of the technological aptitude of lactic acid bacteria to ferment table olives excluding, cheaply and easily, all those strains definitely unable to act as starter. The use of olive paste as a screening medium allows the resistance of the new isolates against olive phenolic compounds to be tested. The selection of strains able to increase the antioxidant power of olive paste can improve the shelf-life of table olives.